(untitled) (International Journal of Food and Nutritional Sciences, 2021)
From the past year, Online Examination has become most popular in all the educational fields due to covid-19 However, the institutions are facing a big difficulty in terms of proctoring methods. If the way we are living is to be the new normal then there is a need to find some solution. In this project, we have proposed a solution that to develop an AI-based integrated system that can helps to preventing cheating in examinations and we present some techniques and tools through which the proctor need not to be present throughout the exam. Our AI-based model will be able to detect any unfair in an examination.